Computer-based system to assess efficacy of stuttering therapy techniques - Chia Ai, Ooi; Yunus, Jasmy (Springer, 2006)
This paper presents a computer-based system tool used to assess efficacy of stuttering therapy techniques. The software assists Speech-Language Pathologist (SLP) in determining suitable techniques for each client. The project implements Digital Signal Processing (DSP)techniques to analyze speech signals and incorporates standard speech fluency shaping techniques that can be used as part of fluency rehabilitation regimen. The software provides real-time visual and audio feedbacks for clients to be aware of their speech patterns. It provides self training aid for clients that motivates them to practice at home. The software runs under Windows XP on a computer equipped with multimedia capabilities. Real-time visual and audio displays enable the clients to compare their average magnitude profiles (AMPs) with clinician’s and alter their speech to match clinician’s AMP. The start and end alignment, maximum magnitude and duration of two AMPs are compared. A score is assigned to each category. The software is developed using Microsoft Visual C++ 6.0. Software is designed as graphic user interface (GUI), which makes therapy user friendly. Three techniques that are implemented in the project have been decided through the discussion with SLP in Hospital Sultanah Aminah (HSA). The techniques are Shadowing, using a Metronome (Taping) and Delayed Auditory Feedback (DAF). This project is done in collaboration with HSA where the hospital assists in the clinical trial.